Analyzing the articles published in the field of flute in Turkey: Türkiye’de flüt alanında yayımlanan makalelerin incelenmesi - Tankız, Kübra Dilek; Caf, Güney (Journal of Human Sciences, 2023)
This study, which aims to examine the articles published in the field of flute in Turkey in terms of various characteristics and to determine the current situation, was designed in descriptive survey model. The 103 articles, which can be accessed by typing the keyword "flute" in Google Scholar, Dergipark, Sobiad databases and Google search engine, were analyzed with a descriptive analysis approach according to the variables of "field, year, subject, method, number of authors, composer studied, journal in which it was published, index in which it was indexed". According to the results of the research, it was determined that the articles published in the field of flute showed a balanced distribution in terms of field type in the field of flute education and outside the field of flute education, were mostly published in 2019, focused on flute techniques, especially on work analysis and etude/method analysis, mainly adopted qualitative method and survey model as method type, mostly single-authored, and W.A. Mozart and E. Köhler were the leading composers covered in their subjects. In addition, it was concluded that these articles, which were published in 52 different journals, were mostly indexed in indexes other than international field indexes, TR Index and journals that are not indexed in any index, and least indexed in journals in ESCI- Scopus and H.W. Wilson indexes, which are known as international field indexes. (Extended English summary is at the end of this document) Özet Türkiye’de flüt alanında yayımlanan makalelerin çeşitli özellikleri açısından incelenmesi ile mevcut durumunun belirlenmesi amacını taşıyan bu araştırma, betimsel tarama modelinde tasarlanmıştır. Google Akademik, Dergipark, Sobiad veri tabanlarına ve Google arama motoruna "flüt" anahtar kelimesi yazılarak ulaşılabilen 103 makale, betimsel analiz yaklaşımı ile "alan, yıl, konu, yöntem, yazar sayısı, işlenilen besteci, yayımlandığı dergi, tarandığı index (dizin) değişkenlerine göre dağılımları incelenmiştir. Araştırmanın sonuçlarına göre flüt alanında yayımlanan makalelerin alan türü bakımından flüt eğitimi alanında ve flüt eğitimi alanı dışında dengeli bir dağılım gösterdiği, en fazla 2019 yılında yayımlandığı, flüt teknikleri başta olmak üzere eser inceleme ve etüt/metot inceleme konuları üzerine yoğunlaştığı, ağırlıklı olarak nitel yöntemi ve yöntem türü olarak tarama modelini benimsediği, çoğunlukla tek yazarlı olduğu, konularında işlenen bestecilerin başında W.A. Mozart ve E. Köhler geldiği tespit edilmiştir. Ayrıca, 52 çeşit dergide yayımlanan bu makalelerin en çok sırasıyla uluslararası alan indexleri dışındaki diğer indexlerde, TR Dizin’de ve hiçbir indexte taranmayan dergilerde dizinlendiği; en az ise uluslararası alan indexleri olarak bilinen ESCI- Scopus ve H.W. Wilson indexleri kaspamındaki dergilerde tarandığı sonuçlarına ulaşılmıştır.